ERK5 Inhibition Induces Autophagy-Mediated Cancer Cell Death by Activating ER Stress - Gámez-García, Andrés; Bolinaga-Ayala, Idoia; Yoldi, Guillermo; Espinosa-Gil, Sergio; Diéguez-Martínez, Nora; Megías-Roda, Elisabet; Muñoz-Guardiola, Pau; Lizcano, Jose M. (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is a highly conserved intracellular process that preserves cellular homeostasis by mediating the lysosomal degradation of virtually any component of the cytoplasm. Autophagy is a key instrument of cellular response to several stresses, including endoplasmic reticulum (ER) stress. Cancer cells have developed high dependency on autophagy to overcome the hostile tumor microenvironment. Thus, pharmacological activation or inhibition of autophagy is emerging as a novel antitumor strategy. ERK5 is a novel member of the MAP kinase family that is activated in response to growth factors and different form of stress. Recent work has pointed ERK5 as a major player controlling cancer cell proliferation and survival and, therefore small-molecule inhibitors of ERK5 have shown promising therapeutic potential in different cancer models. Here, we report for the first time ERK5 as a negative regulator of autophagy. Thus, ERK5 inhibition or silencing induced autophagy in a panel of human cancer cell lines with different mutation patterns. As reported previously, ERK5 inhibitors (ERK5i) induced apoptotic cancer cell death. Importantly, we found that autophagy mediates the cytotoxic effect of ERK5i, since ATG5ˉ/ˉ autophagy-deficient cells viability was not affected by these compounds. Mechanistically, ERK5i stimulated autophagic flux independently of the canonical regulators AMPK or mTORC1. Moreover, ERK5 inhibition resulted in ER stress and activation of the Unfolded Protein Response (UPR) pathways. Specifically, ERK5i induced expression of the ER luminal chaperone BiP (a hallmark of ER stress), the UPR markers CHOP and ATF4, and the spliced form of XBP1. Pharmacological inhibition of UPR with chemical chaperone TUDC, or ATF4 silencing, resulted in impaired ERK5i-mediated UPR, autophagy and cytotoxicity. Overall, our results suggest that ERK5 inhibition induces autophagy-mediated cancer cell death by activating ER stress. Since ERK5 inhibition sensitizes cancer cells and tumors to chemotherapy, future work will determine the relevance of UPR and autophagy in the combined use of chemotherapy and ERK5i to tackle cancer.